Ethnic conflict and economic disparity: Serbians and Albanians in Kosovo - Sumon Kumar Bhaumik; Ira N. Gang; Myeong-Su Yun (Institute for the Study of Labor (IZA), 2005)
We use the Living Standards Measurement Study (LSMS) household survey from post-conflict Kosovo to examine economic deprivation among Serbs and Albanians. Economic deprivation is measured by per capita household expenditure and by the incidence of poverty as captured by the headcount ratio. We examine the roles played by the stock of attributes and by the impact of these attributes on deprivation using Oaxaca-type decomposition methods. Empirical results for both decomposition analyses show differences in characteristics as well as returns to measured characteristics favor Serbs, even though Serbs have lower expenditures and higher poverty incidence than Albanians.
Keywords: I32; O12; J15; 330; poverty; ethnicity; decomposition; Sozialer Konflikt; Ethnische Gruppe; Armut; Kosovo; Soziale Ungleichheit